Two Tryptophans Are Better Than One in Accelerating Electron Flow through a Protein - Takematsu, Kana; Williamson, Heather R; Nikolovski, Pavle; Kaiser, Jens T; Sheng, Yuling; Pospíšil, Petr; Towrie, Michael; Heyda, Jan; Hollas, Daniel; Záliš, Stanislav; Gray, Harry B; Vlček, Antonín; et al. (ACS central science, 2019)
We have constructed and structurally characterized a Pseudomonas aeruginosa azurin mutant Re126WWCuI , where two adjacent tryptophan residues (W124 and W122, indole separation 3.6-4.1 Å) are inserted between the CuI center and a Re photosensitizer coordinated to the imidazole of H126 (ReI(H126)(CO)3(4,7-dimethyl-1,10-phenanthroline)+). CuI oxidation by the photoexcited Re label (*Re) 22.9 Å away proceeds with a ∼70 ns time constant, similar to that of a single-tryptophan mutant (∼40 ns) with a 19.4 Å Re-Cu distance. Time-resolved spectroscopy (luminescence, visible and IR absorption) revealed two rapid reversible electron transfer steps, W124 → *Re (400-475 ps, K 1 ≅ 3.5-4) and W122 → W124•+ (7-9 ns, K 2 ≅ 0.55-0.75), followed by a rate-determining (70-90 ns) CuI oxidation by W122•+ ca. 11 Å away. The photocycle is completed by 120 μs recombination. No photochemical CuI oxidation was observed in Re126FWCuI , whereas in Re126WFCuI , the photocycle is restricted to the ReH126W124 unit and CuI remains isolated. QM/MM/MD simulations of Re126WWCuI indicate that indole solvation changes through the hopping process and W124 → *Re electron transfer is accompanied by water fluctuations that tighten W124 solvation. Our finding that multistep tunneling (hopping) confers a ∼9000-fold advantage over single-step tunneling in the double-tryptophan protein supports the proposal that hole-hopping through tryptophan/tyrosine chains protects enzymes from oxidative damage.